From phase drift to synchronisation – pedestrian stepping behaviour on laterally oscillating structures and consequences for dynamic stability. (31st March 2017) - Bocian, Mateusz; Burn, Jeremy F.; Macdonald, John H.G.; Brownjohn, James M.W.
Abstract: The subject of this paper pertains to the contentious issue of synchronisation of walking pedestrians to lateral structural motion, which is the mechanism most commonly purported to cause lateral dynamic instability. Tests have been conducted on a custom-built experimental setup consisting of an instrumented treadmill laterally driven by a hydraulic shaking table. The experimental setup can accommodate adaptive pedestrian behaviour via a bespoke speed feedback control mechanism that allows automatic adjustment of the treadmill belt speed to that of the walker. 15 people participated in a total of 137 walking tests during which the treadmill underwent lateral sinusoidal motion. The amplitude of this motion was set from 5 to 15 mm and the frequency was set from 0.54 to 1.1 Hz. A variety of stepping behaviours are identified in the kinematic data obtained using a motion capture system. The most common behaviour is for the timing of footsteps to be essentially unaffected by the structural motion, but a few instances of synchronisation are found. A plausible mechanism comprising an intermediate state between unsynchronised and synchronised pedestrian and structural motion is observed. This mechanism, characterised by a weak form of modulation of the timing of footsteps, could possibly explain the under-estimation of negative damping coefficients in models and laboratory trials compared with previously reported site measurements. The results from tests conducted on the setup for which synchronisation is identified are evaluated in the context of structural stability and related to the predictions of the inverted pendulum model, providing insight into fundamental relations governing pedestrian behaviour on laterally oscillating structures. Highlights: Most often the timing of footsteps is unaffected by structural motion. Walking on laterally oscillating ground can change timing of pedestrian footsteps. Phase pulling is discovered for the first time in experimental data. It can explain underestimation of self-excited forces in previous studies. Synchronisation is not the main mechanism causing structural instability.